The Relationship between Islamic Corporate Governance, Human Governance and Sustainability Reporting of Shariah Compliant Companies in Malaysia - Nurul Nazlia Jamil; Dato' Hasnah Hj Haron; Nathasa Mazna Ramli; Sumaiyah Abd Aziz; Syahnaz Sulaiman; Anderes Gui (Human Resource Management Academic Research Societ, 2024)
Vol. 12, No. 2, 2022, Pg. 621 - 642